Comparison of two methods of irrigant agitation in the removal of residual filling material in retreatment - Clarissa Teles Rodrigues; Marco Antonio Hungaro Duarte; Bruno Martini Guimarães; Rodrigo Ricci Vivan; Norberti Bernardineli (Brazilian Oral Research, 2017)
Abstract: The aim of this study was to compare the efficacy of passive ultrasonic irrigation and EasyClean for removing residual filling material in retreatment. Twenty-two maxillary lateral incisors with apical curvature were instrumented with ProTaper files and filled with Endofill using the lateral compactation technique. Removal of filling material was performed with Reciproc, Mtwo and ProDesign Logic 50/.01 files. The teeth were inserted in a silicone mould, which was placed in a metal muffle, and split to visualize the residual filling material. The samples were divided into two groups (n = 11) according to the irrigation protocol: Passive ultrasonic irrigation (PUI group) with 3 activations of 20 seconds and EasyClean (Easy Equipamentos Odontológicos, Belo Horizonte, Brazil) (EC group) used in continuous rotation with 3 activations of 20 seconds, both using NaOCl and EDTA. Environmental scanning electron microscopic images of the apical, middle, and cervical thirds were taken before and after the irrigant activation. The Kappa test was used to determine interexaminer agreement. Statistical analysis was performed using Kruskal–Wallis, Mann–Whitney, and Wilcoxon tests (p < 0.05). PUI and EC improved the removal of remnant filling material in all root canal thirds (p < 0.05). PUI and EC presented similar performance in the final step of retreatment (p > 0.05). No significant difference was observed in the removal of filling material in the apical, middle, and cervical thirds in both groups (p > 0.05). EasyClean in continuous rotary motion is useful in retreatment and was shown to be as effective as ultrasonic activation in the removal of remnant filling material.